68.4k views
3 votes
6,2 x 10^2 = 0 x t + 1/2 x (-9/8) t^2 + 2582,91

1 Answer

0 votes

Answer:

Step-by-step Step-by-step explanation:

  • 6,2 × 10² = 0 × t + ½ × (-9/8) × t² + 2582,91

  • 6,2 × 100 = 0 + ½ × (-9/8) × t × t + 2582,91

  • 620 = ½ × (-9/8) × t × t + 2582,91

  • 620 = (-9/16) × t × t + 2582,91

  • 620 = (-9/16 t²) + 2582,91

  • 620 ≠ 1.032.939/400 t²

  • 6,2 × 10² ≠ 0 × t + ½ × (-9/8) × t² + 2582,91

Conclusion:

6,2 × 10² ≠ 0 × t + ½ × (-9/8) × t² + 2582,91


User Ivan Voras
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.